Magnetic resonance enterography in Crohn’s disease: How we do it and common imaging findings - Mantarro, Annalisa (World J Radiol, 2017)
Crohn’s disease (CD) is a chronic inflammatory disease of the gastrointestinal tract, with unpredictable clinical course by phases of relapses alternating with other of quiescence. The etiology is multifactorial and is still not completely known; globally the westernization of lifestyle is causing an increasing incidence of CD, with peak age of 20-30 years. The diagnostic workup begins with the evaluation of the clinical history, physical examination and laboratory tests. However, the clinical assessment is subjected interobserver variability and, occasionally, the symptoms of acute and chronic inflammation may be indistinguishable. In this regards, the role of magnetic resonance (MR) enterography is crucial to determine the extension, the disease activity and the presence of any complications without ionizing radiations, making this method very suitable for young population affected by CD. The purpose of this review article is to illustrate the MR enterography technique and the most relevant imaging findings of CD, allowing the detection of small bowel involvement and the assessment of disease activity.